A Model for Implementing New FinTechs in the Banking Industry (Peer-to-Peer Lending) - Hosein Mohammadi; Narges Mohammadalipour; Noroz Norollahzadeh; Ghanbar Abbaspour asfadan; Mahnaz Rabie (ارزش آفرینی در مدیریت کسب و کار)
Abstract The aim of the current research is to present a model for the implementation of new fintechs in the banking industry (peer-to-peer lending). The research method is applicable in terms of purpose, mixed (qualitative-quantitative) in terms of implementation, and survey in terms of nature and method. The statistical population of the research was the managers, supervisors and employees of the financial and technological fields of banks, experts and specialists in the fintech field in the country; and according to the principles and rules of the unlimited population, 384 people were selected as a sample. Data collection was done by semi-structured interviews in the qualitative part, and by the researcher-made questionnaire in the quantitative part. Coding and MAXQDA software were used in qualitative part data analysis, and SPSS and AMOS software were used in quantitative part. The results of the qualitative data analysis of the research were categorized as follows: In this regard, the extracted categories were categorized as follows: Causal conditions: organizational learning, system attitude, and information technology. Key conditions: communication capital, human capital, and structural capital. Governing platform: partner banks, external theorists, government, and environmental conditions. Intervening conditions: obstacles and challenges including organizational factors, community conditions, individual factors, and lack of education and research. Strategies: policy making, strategic plan, and employee satisfaction and loyalty. Consequence: knowledge-based policy making, knowledge management, innovation, creativity and idea, and knowledge-based organization. The results of the quantitative part showed that the fit indices of the model indicate the confirmation of the model at the confidence level of 99%. Extended Abstract Introduction Among the advantages of strategic cooperation between the banking system and fintech is efficiency in terms of speed, cost, and reaching new customers. The issues and problems of traditional banks include complex structures, high level of formality, increase in operational cost, providing banking services with more cost and time, lack of innovation in service, and failure to meet customer expectations (Soltanee & Tahmasebi Aghbolaghi, 2020). All these factors have led to the decrease in the popularity of the banking system; But on the other side of the field, the increase of people who, for various reasons, cannot use traditional banking services or do not want to use them, has led to the development of fintechs. This trend has confirmed the decreasing popularity of banks, and according to statistics, the average use of fintech globally has reached 33% (Hill, 2018). Peer-to-peer lending in modern banking is a co-product of important business, technological and social processes. One item that has helped to create peer-to-peer lending is the presence of a new generation of freedom advocates. "Technological changes, globalization, and other international processes have reduced the number, size and role of commercial intermediaries in many industrial sectors. These changes have also led to the emergence of peer-to-peer lending. Individuals can become members as lenders by registering on the peer-to-peer lenders website." (Sarhangi et al, 2016). Borrowers also enjoy the benefits of lower costs compared to bank or credit union loans. Fintechs can provide new products and services for peer-to-peer banking customer groups that do not have access to traditional financial services. These conditions are possible through the following ways: improving financial participation, providing simple products with low cost and helping people who do not have easy access to banking services, and improving the customer experience, increasing transparency and improving security, and accommodating retail customers and small and moderate companies to fraudity and cyber-attacks (Wonglimpiyarat, 2017). Due to the importance of this issue, this research seeks to present and propose a suitable model for the implementation of new fintechs in the banking and peer-to-peer lending industry. In this research, we are looking for an answer to this question: what is the implementation model of new fintechs in the banking industry (peer-to-peer lending)? Theoretical Framework fintech The term fintech means financial technology. Fintech refers to companies and representatives of companies that have combined financial services with modern innovative technology. Usually, new participants in the market offer Internet products and application-based products (Anil & Alistair, 2019). Fintech or financial technology is a set of businesses that use software and hardware to provide innovative financial services. The National Center for Digital Research in Dublin, Ireland defines fintech as innovation in financial services (Owzaei & Sohrabi, 2017). Sadraee et al, (2024) examines the presentation of the fintech market development model with an emphasis on existing challenges and strategies. The results of the research showed that the challenges of fintech market development include insufficient infrastructure, regulatory and legislative barriers, difficulty working with public/general customers, mistrust of technology and fintech, low income levels and product pricing challenges, and cultural barriers. Also, fintech market development strategies include community participation in the marketing process, use of social networks, smart and optimal advertising, useful and valuable content production, branding, adaptation of communication strategies to the nature of the fintech market, geographic and cultural segmentation of the market, as well as customer education. Khaled Mohammad et al, (2023) investigated the determinants of fintech adoption: evidence from a representative sample of emerging economies across the country. They identified important characteristics that predict customer fintech adoption among individual respondents. They found that customers were less likely to adopt fintech services if they reported higher levels of concern about security, information privacy, limited government control, and higher levels of perceived service barriers. Evidence showed that these concern factors, for example, are the main determinants of fintech adoption, unlike demographic variables. Our findings have insights for fintech service providers and policy makers.